محاولة إيجاد طرق جديدة لصناعة المركبات النانوية - مجدي بوصبيع إبراهيم - مناني محمد السعيد (university of eloued جامعة الوادي, 2024)
تقنية النانو واصطناع المواد النانوية تمثل إحدى التطورات البارزة في مجال العلوم والتكنولوجيا الحديثة، حيث تركز على دراسة وتطوير المواد على مستوى النانومتر، ما يضفي عليها خصائص فريدة تجعلها مثيرة للاهتمام في عدة تطبيقات متنوعة. تتم استخدام طرق متعددة لإنتاج هذه المواد، بما في ذلك الطرق الكيميائية والفيزيائية والبيولوجية، مما يمنح القدرة على التحكم الدقيق في الخصائص والأداء. وتشمل أحدث التطورات استخدام مواد طبيعية مثل الخميرة والنشاء لإنتاج المواد النانوية، مما يساهم في الاستدامة ويحد من الآثار البيئية السلبية. يتم تحليل وتشخيص هذه المواد باستخدام تقنيات حديثة مثل المجهر الإلكتروني والتحليلات الطيفية والاشعاعات الضوئية المغناطيسية ، لفهم خصائصها بدقة. تطبيقاتها الحالية تشمل تطوير الأدوية النانوية وتحسين أداء الأجهزة الإلكترونية، وتظهر الآفاق المستقبلية توسيع استخداماتها في مجالات الطاقة المتجددة والحفاظ على البيئة، مما يجعلها مجالاً واعداً للبحث والابتكار. Nanotechnology and nanotechnology represent one of the notable developments in the field of modern science and technology, focusing on the study and development of nanometer-level materials, giving them unique characteristics that make them interesting in several diverse applications. Multiple methods are used to produce these materials, including chemical, physical and biological methods, giving the ability to accurately control the characteristics and performance. The latest developments include the use of natural materials such as yeast and starch to produce nanomaterials, which contributes to sustainability and reduces negative environmental impacts. These materials are analyzed and diagnosed using modern techniques such as electron microscopy, spectral analyses and magnetic optical radiation, to accurately understand their properties. Its current applications include the development of nanopharma and the improvement of the performance of electronic devices, and future prospects show the expansion of its uses in the areas of renewable energy and environmental conservation, making it a promising area for research and innovation.
مدكرة ماستر كيمياء
Keywords: لمواد النانوية-النانومتر-الخميرة-النشاء-المجهر الإلكتروني-التحليلات الطيفية والمغناطيسية فرنسيــة او إنجليزية: Nanomaterials-nanomaterials-yeast-starch-electron microscope-spectral and